The Development Of Auditory-cognitive Training Materials In Malay Language Intended For Older Adults With Normal And With Neuro-cognitive Impairment - Yusmeera Yusof; Siti Zamratol-Mai Sarah Mukari; Mariam Adawiah Dzulkifli; Kalaivani Chellapan; Aminah Awang Besar; Kartini Ahmad; Nashrah Maamor; Wan Syafira Ishak; Nurhafizah Mohd. Sukor (IIUM Press, 2024)
Non-Indexed Publication